Análise do mercado internacional de compensado - Ribeiro, Ivonise Silva Andrade (2003)
This research analyzes plywood international market considering the main importers and exporters. The world market was modeled to simulate changes in production, flow and prices caused by shocks in the exogenous variables such as changes in the of supply and demand. The chosen model assumes that imports are differentiated by locals of production, i. e., such products are not perfect substitutes. The results suggest that exogenous changes that stimulates demand growth in one market may increase product prices of those countries with higher participation in that market. The less expressive countries in such market may have their products prices even downed and may benefit more of the commercial flow. An exogenous increase in the Japanese plywood demand causes higher increase in the Malaysian and Indonesian price as compared to other suppliers, due to the intense flow of this product between these countries and Japan. However an increase in the USA demand, Brazilian and Canadian prices increases more than the prices of the other export countries due to the higher participation of Brazil and Canada in the global market. An increase in German plywood demand benefits more the commercial flow of Finland, Italy and Australia, in terms of price increase, due to their higher participation in German plywood market. An exogenous increase in the European plywood market affect markedly price an volume, of plywood international market. Export countries drive their exports to European countries, reducing their exports to USA and Japan. An exogenous increase in the plywood supply of an specific country cause a reduction in its product price, allowing an increase in its market share. A combination of exogenous increase of plywood supply in Brazil, Malaysia and Indonesia result in a sharper decrease in the Brazilian plywood price, as compared to a decrease in other countries. The availability of Brazilian plywood increase significantly its consumption in all other countries. If it is assumed that plywood supply reacts promptly to price changes (inelastic supply), long run simulations effects are similar to short run ones.